First Episode of Psychosis in a Middle-Aged Patient with a 14-Year History of Conversion Disorder - Peritogiannis, Vaios; Manthopoulou, Thiresia; Mavreas, Venetsanos (Case Reports in Psychiatry, 2014)
We present a case of a middle-aged male patient with a long history of conversion disorder and histrionic personality, who presented with newly onset psychotic symptoms while being engaged to treatment with a community mental health team in a primary care setting. The symptoms could not be attributed to an organic cause. After a short course of olanzapine treatment which caused adverse effects, the symptomatology responded well to low dose amisulpride. Conversion symptoms were stable throughout the psychotic episode. This case illustrates the complex interplay between disorders classified in different categories (somatoform versus psychotic disorders).